2011
DOI: 10.1523/jneurosci.3020-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Functional Dissociation of Hippocampal Mechanism during Implicit Learning Based on the Domain of Associations

Abstract: Traditionally, the medial temporal lobe (MTL) was linked to explicit or declarative memory in associative learning. However, recent studies have reported MTL involvement even when volunteers are not consciously aware of the learned contingencies. Therefore, the mechanism of the MTL-related learning process cannot be described sufficiently by the explicit/implicit distinction, and the underlying process in the MTL for associative learning needs a more functional characterization. A possible feature that would a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
79
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 45 publications
(58 reference statements)
13
79
2
Order By: Relevance
“…As mentioned above, this had already been shown some time ago by Rose et al (2002Rose et al ( , 2004 for the medial temporal lobe. More recently, this finding has been confirmed for the hippocampus proper in the NRT (Darsaud et al, 2011) and in the SRTT (Rose, Haider, Salari, & Büchel, 2011).…”
Section: Sleep-eeg Resultsmentioning
confidence: 57%
“…As mentioned above, this had already been shown some time ago by Rose et al (2002Rose et al ( , 2004 for the medial temporal lobe. More recently, this finding has been confirmed for the hippocampus proper in the NRT (Darsaud et al, 2011) and in the SRTT (Rose, Haider, Salari, & Büchel, 2011).…”
Section: Sleep-eeg Resultsmentioning
confidence: 57%
“…Data, however, suggest that these two memory systems interact in either a synergistic or competitive manner (Gheysen et al, 2011;Rose et al, 2011;Sadeh et al, 2011;Schott et al, 2006;Seger et al, 2011), depending on task demands (Delgado and Dickerson, 2012;Packard and Goodman, 2012;Poldrack and Foerde, 2008). Specifically, the declarative memory system involves the MTL cooperating with the ventromedial prefrontal cortex (Preston and Eichenbaum, 2013), and enables instance learning, the extraction and application of underlying associative or categorical rules (generalization) to new instances, as well as retrieval of ensuing episodic and semantic memories (Hoscheidt et al, 2010).…”
Section: Declarative Memorymentioning
confidence: 99%
“…Thus, it was predicted that the caudate and MTL would also be involved in the implicit task-irrelevant perceptual sequence learning. Furthermore, previous SRT studies showed that the implicit sequence learning was characterized by the incremental gains of performance rather than an all-or-none phenomenon (unlike learning about facts) (Gheysen et al 2010) and the activation pattern of the neural regions which were crucial to implicit sequence learning (i.e., caudate and/or hippocampus) matched with the behavioral pattern (Gheysen et al 2010;Rose et al 2011). Therefore, we predicted that better behavioral learning performance and greater learningrelated activations in hippocampus and caudate would be found in the later stage of the SSI task relative to the early stage.…”
Section: Introductionmentioning
confidence: 96%
“…A growing number of studies have investigated this issue and reported controversial results (Deroost and Soetens 2006;Gheysen et al 2009;Prinz 1993, 1997;Remillard 2003Remillard , 2009Stöcker et al 2003;Willingham 1999;Willingham et al 2000;Ziessler 1998;Ziessler and Nattkemper 2001). Recently, Rose et al (2011) developed a novel SRT task which dissociated the different modalities (perceptual and motor) of sequence learning, thus avoiding possible confounding between perceptual sequence learning and motor sequence learning. In their study, six colored squares were presented around the center of the screen, where the target square appeared simultaneously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation